[The Multidisciplinary Management of Type 2 Diabetes: an Integrated Care Model] - Berra, Cesare Celeste; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2021)
Over the past 20 years, the prevalence of diabetes in Italy has been growing, up to the current estimated proportion of about 8.5%, which accounts also for undiagnosed patients. As most of these subjects are >65 years of age, the probability of having comorbidities is high. In addition, diabetes itself exposes patients to a wide spectrum of complications, that cover several therapeutic areas. This is why the optimal management of diabetes necessarily involves a multidisciplinary team. Several models of integrated care of chronic diseases may be set: for instance, the role assigned to GPs and specialists may differ among models. Indeed, a disequilibrium between GPs and specialists is deemed to be the main cause of the low patients’ participation in Progetto Cronicità (chronic diseases project), which started in Lombardia (a Northern region in Italy) in 2018. A help to understand how to build a proper integrated care model in diabetes comes from the experience of the Authors, that describe in detail their experience in IRCCS MultiMedica (Sesto San Giovanni, MI, Italy). This Supplement ends with a review of the evidence found in literature about the advantages of a multidisciplinary management of diabetes in terms of outcomes, costs, and patients’ satisfaction.